Characterization of urinary bioactive phenolic metabolites excreted after consumption of a cup of mountain tea (Sideritis scardica) using liquid chromatography – tandem mass spectrometry - Petreska Stanoeva, Jasmina; Bagashovska, Daniela; Stefova, Marina (Society of Chemists and Technologists of Macedonia, 2012)
A nutrition experiment was performed for studying the bioavailability of polyphenols from Sideritis with healthy human subjects, who consumed a standardized Sideritis decoction after which urine was collected and analyzed. 35 polyphenolic compounds in the ingested decoction and 63 of their metabolites in urine collected after ingestion were identified using HPLC/MSn. It was shown that polyphenols present in Sideritis decoction are extensively conjugated to glucuronides, sulfates and also transformed to methylated forms after oral administration. In the analyzed urine samples, 31 different metabolites of hypolaetin, methylhypolaetin, isoscutellarein, methylisoscutellarein and apigenin, and 32 phenolic acids metabolites were detected, hypolaetin and isoscutellarein metabolites being the most abundant. This enabled polyphenols metabolites patterns to be obtained, which is a crucial step towards revealing the bioavailability and metabolism of phenolic compounds from Sideritis in human. The identification and structure elucidation of these metabolites provided essential data for further studies of Sideritis polyphenols bioavailability.